Japan’s Low-growth Economy from the Viewpoint of Energy Quality - Nakajima, Yuka; Matsushima, Jun (International Journal of Energy Economics and Policy, 2022)
To investigate the possible cause of Japan’s low-growth economy, we analyze the correlation between the quality of energy and economic production such as real GDP (Gross Domestic Product) and energy intensity over the 52-year period from 1965 to 2017. Corrections are made for the quality of energy using two approaches—a physical-based quality correction (i.e., transformity) and an economics-based quality correction. We find that energy quality affects economic production, and that real GDP correlates with quality-corrected final energy consumption. We imply that economic inactivity due to the decline in energy acquisition capacity represented by the decline in societal-scale EROI (Energy Return on Investment) may be directly linked to the low economy growth. We also find that the energy intensity decreases as the quality of energy used improves, and that regardless of quality correction, the energy intensity decreases as the electrification rate increases. Finally, we conclude that the quantity and quality of energy are closely related to the performance of the Japanese economy and point out the importance of energy quality in Japan—a country that has a low energy self-sufficiency rate in an era when the supply of energy is being depleted.